Three new earthworm species of the genus Metaphire Sims & Easton, 1972 (Oligochaeta, Megascolecidae) from Dong Nai Province, Vietnam - Tung, Nguyen Thanh; Dang, Lam Hai (Academia Journal of Biology, 2017)
Three new earthworm species are described from Dong Nai Province, Vietnam, namely Metaphire malayanoides sp. n., Metaphire grandiverticulata sp. n., and Metaphire xuanlocensis sp. n. Both M. malayanoides sp. n. and M. grandiverticulata sp. n. have four pairs of spermathecal pores in ventrolateral 5/6/7/8/9. However, M. malayanoides is distinguished by having two to eight pairs of genital markings located in intersegmental furrows, starting from 19/20; M. grandiverticulata sp. n. is characterized by having only one pair of genital markings between male porophores in xviii, and very large tube-shaped diverticulum. M. xuanlocensis sp. n. has one pair of spermathecal pores inside the spermathecal chambers in 7/8, accessory glands stalked and attached to the enlarged base of protastic duct, and the presence of penial setae. Citation: Nguyen Thanh Tung, Lam Hai Dang, 2017. Three new earthworm species of the genus Metaphire Sims & Easton, 1972 (Oligochaeta, Megascolecidae) from Dong Nai Province, Vietnam. Tap chi Sinh hoc, 39(4): 406-415. DOI: 10.15625/0866-7160/v39n4.10627.*Corresponding author: thanhtung@ctu.edu.vnReceived 17 August 2017, accepted 20 November 2017